The Development Strategy of Muhammadiyah School in Based Conservative-NU Society - Zainal Arifin (Balai Penelitian dan Pengembangan Agama Semarang, 2013)
The existence of Aisyiyah Kindergarten (Aisyiyah Bustanul Athfal) and Muhammadiyah Elementary School at Mlangi Sleman Yogyakarta, where the majority of the community are from Nahdlatul Ulama (NU), that cause some social conflicts. However, the Aisyiyah Kindergarten and Muhammadiyah Elementary School are still be the favorite school at Mlangi. In fact, there are 23 pesantren based on NU, Masyitoh Kindergarten, 2 islamic elementary school belong to an-Nasyat and al-Falahiyah and NU Elementary School. This research discussed on obstacles, conflict, format of solutions, and development strategy of Aisyiyah Kindergarten and Muhammadiyah Elementary School at Mlangi. This research is a qualitative study used in-depth interview, observation, and documentation. The results showed the barriers and conflicts experienced by Aisyiyah Kindergarten and Muhammadiyah Elementary School in Mlangi, they are: parents’ low attention on formal education, clash of school activities and pesantren activities, limited infrastructure, limited human resources, negative thinking of Mlangi community on Aisyiyah Kindergarten and Muhammadiyah Elementary School, the difference in religious teaching, and the new admission competition. Development strategy of Aisyiah Kindergarten and Muhammadiyah Elementary School in Mlangi include imaging, increasing extra curricular program, improving infrastructure facilities, accomodating local culture, and providing tolerance and accomodation for students with different culture.